2010
DOI: 10.1177/1476718x10366773
|View full text |Cite
|
Sign up to set email alerts
|

Pediatricians’ perspectives on identification and diagnosis of autism spectrum disorders

Abstract: Qualitative interview methodology was used to investigate the perspectives and experiences of five general pediatricians who had diagnosed children with autism spectrum disorder (ASD). Information was obtained from the participants in the following areas: a) training; b) signs/symptoms of ASD; c) causes of ASD; d) well-child exams; e) first concerns/signs of ASD; f) use of 'wait and see'; g) communication with families; h) making referrals; i) the diagnostic process for ASD; j) pediatrician comfort with making… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 11 publications
0
21
0
1
Order By: Relevance
“…The parents whose children are diagnosed with ASD are more streesed than the parents whose children receive the diagnosis of any developmental disorder (Gupta & Singhhal, 2005). In the study carried out by Finke et. al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The parents whose children are diagnosed with ASD are more streesed than the parents whose children receive the diagnosis of any developmental disorder (Gupta & Singhhal, 2005). In the study carried out by Finke et. al.…”
Section: Discussionmentioning
confidence: 99%
“…The number of studies which investigate the opinions and suggestions of physicians about diagnosing ASD is very limited. In some of these studies, the doctors who diagnosed children with ASD identified and offered recommendations for the existing limitations in the US (Finke et al, 2010;Flippek et al, 2000;Penner et al, 2017). There is also a limited number of studies which examined the opinions of Turkish-speaking families and experts in the diagnostic process of ASD (Gürel-Selimoğlu et al, 2013;Karaaslan & Karaaslan, 2016).…”
Section: The Problemmentioning
confidence: 99%
“…They further stated that their pediatricians provided information related to various health problems seen in early childhood, irritability, retardation in motor development, and sensory sensitivity [6]. In a study investigating the opinions and experiences of physicians, pediatricians stated that they did not feel comfortable when they established a diagnosis without consulting a specialist experienced in autism [16]. All these findings suggest that pediatricians are successful in identifying problems in children, but they lack information, which has been previously suggested but now begins to lose their validity, regarding the issues specific to autism, matters of concern to families, or issues related to the causes of autism.…”
Section: Discussionmentioning
confidence: 99%
“…Physicians stated that one of these reasons was that they did not receive sufficient training on ASD in medical faculties and during their residency. Secondly, they stated that they did not have sufficient time and opportunity to attend inservice training or meetings to obtain information about the diagnosis of children with ASD [16]. In another study from Turkey, specialists mentioned that they were having difficulties due to problems such as insufficiency of the duration for the diagnosis, lack of biological marker in the diagnosis, lack of following the neuro-motor development of the child, insufficiency of the special education services for the children with autism, the commercialization of the foundations giving education services in autism, and lack of informing the parents about autism [17].…”
Section: Discussionmentioning
confidence: 99%
“…However, current practice parameters aim to support the effort to identify ASD at a young age so that intervention may begin early, as intervention for ASD may lead to better outcomes when it begins at younger ages [e.g., ( 9 12 )]. In contrast to general pediatric settings, centers focusing on ASD often make the diagnosis at 18 to 24 months of age, but these settings are typically staffed with physicians with specialty training in diagnosing early childhood neurodevelopmental disorders, such as developmental and behavioral pediatricians and pediatric neurologists ( 13 , 14 ). Despite recent improvements, the barriers to early identification and diagnosis of ASD remain significant and the missed opportunities for early and optimal outcomes are profound.…”
Section: Introductionmentioning
confidence: 99%